Prevalence and associated factors of visual impairment among preschool children in selected kindergarten schools in Addis Abeba, Ethiopia,2023 cross-sectional study - Kirubel Asmelash; Hanna Gebre; Girum W. Gebriel Gesese; Yordanos Girma; Hiwot Berhanu Andualem (BMC Public Health)
Abstract Background A child’s vision provides valuable information about the surrounding world. Eye problems in Ethiopia are among the major public health challenges. The prevalence rates of low vision and blindness in Ethiopia are 3.7% and 1.6%, respectively. The American Academy of Pediatrics, in its Recommendations for Preventive Pediatrics Health Care, recommends that ophthalmological evaluation be started from the age of 3 years to 6 years. These recommendations of screening are not being practiced in Ethiopia. With much of visual impairments being due to either preventable or treatable causes, early detection or correction of visual problems at an early age is important. Objectives To determine the prevalence and associated factors of visual impairment among preschool aged children in selected kindergarten schools in Addis Ababa, Ethiopia, from September 29, 2023, to October 29, 2023. Methods A cross-sectional study was conducted in selected preschools located in Addis Ababa. The total sample size was estimated to be 238. A multistage sampling technique was used to select the study participants. Data were collected by trained data collectors via a structured questionnaire and physical examination. The data collected were checked for completeness, cleaned and entered into SPSS version 25 for analysis. Descriptive statistics were computed in frequency tables. Correlation analysis and binary logistic regression were performed to assess factors affecting visual impairment. A P value < 0.05 was considered statistically significant. Result Among the 229 preschool children who participated in this study, 12 had visual impairment, resulting in a prevalence of visual impairment in the selected kindergartens of 5.24%. Maternal alcohol use during pregnancy (AOR = 8.529, 95% CI (1.51–48.02)) and abnormal pen light evaluation (AOR = 18.932, 95% CI (3.85–92.89)) were significantly associated with visual impairment. Conclusion The prevalence of visual impairment in either eye among preschool-aged children residing in Addis Ababa was 5.24%. Maternal Alcohol consumption and abnormal penlight evaluation were factors associated with visual impairment. It has been shown that screening at this age as per the recommendations of the AAP can be beneficial, with many visual impairments being due to either preventable or treatable causes. Clinical trial number Not applicable.